Language policy, power, and educational equity: examining the role of Bahasa Indonesia and local languages in schooling - Muhammad Fauzan Aminudin (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Indonesia’s multilingual educational landscape, characterized by more than 700 local languages coexisting with Bahasa Indonesia as the national language, presents structural tensions between national cohesion and linguistic diversity that significantly affect educational equity. Objective: This study aims to examine how national language policy, classroom practice, and communicative interaction collectively construct linguistic hierarchies that shape access to learning in primary and secondary schooling. Method: Employing a qualitative multi-sited design, this research integrates Critical Discourse Analysis, the Language Policy and Planning framework, and the Ethnography of Communication to analyze policy documents, textbooks, classroom interactions, and teacher interviews from multilingual regions. Results: The findings reveal that policy discourse systematically positions Bahasa Indonesia as the sole legitimate medium of academic recognition. Although translanguaging practices enhance participation and conceptual understanding in exploratory phases, such inclusion remains informally sanctioned. Monolingual assessment regimes ultimately reassert linguistic hierarchy, converting symbolic capital into institutionalized academic advantage. Implication: These findings suggest that achieving educational equity in multilingual Indonesia requires systemic alignment between policy, pedagogy, and assessment to legitimize diverse linguistic resources rather than reinforce monolingual hierarchies. Novelty: This study’s novelty lies in its integrated, multi-layered analytical framework that bridges macro-level discourse, meso-level policy implementation, and micro-level communicative practice, offering a scalable model for examining language, power, and educational equity in multilingual contexts.